Multi-omics-driven development of alternative crops for natural rubber production - Ning YANG; Dan-dan YANG; Xu-chen YU; Cao XU (Journal of Integrative Agriculture, 2023)
Natural rubber (NR) is an irreplaceable biopolymer of economic and strategic importance owing to its unique physical and chemical properties. The Pará rubber tree (Hevea brasiliensis (Willd. ex A. Juss.) Müll. Arg.) is currently the exclusive commercial source of NR, and it is primarily grown in plantations restricted to the tropical and subtropical areas of Southeast Asia. However, current Pará rubber production barely meets the sharply increasing global industrial demand for rubber. Petroleum-based synthetic rubber (SR) has been used to supplement the shortage of NR but its industrial performance is not comparable to that of NR. Thus, there is an urgent need to develop new productive rubber crops with broader environmental adaptability. This review summarizes the current research progress on alternative rubber-producing plants, including horticultural plants (Taraxacum kok-saghyz Rodin and Lactuca L. species), woody plants (Parthenium argentatum A. Gray and Eucommia ulmoides Oliv.), and other plant species with potential for NR production. With an emphasis on the molecular basis of NR biosynthesis revealed by a multi-omics approach, we highlight new integrative strategies and biotechnologies for exploring the mechanism of NR biosynthesis with a broader scope, which may accelerate the breeding and improvement of new rubber crops.